2014
DOI: 10.1186/1471-2334-14-94
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hepatitis B and hepatitis delta viruses circulating in the Western Amazon region, North Brazil

Abstract: BackgroundHepatitis B virus (HBV) and hepatitis D virus (HDV) represent important public health problems in the Western Amazon region with reported cases of fulminant hepatitis. This cross sectional study describes HBV and HDV genotypes circulating in the Brazilian Amazon region.MethodsHBsAg positive individuals (n = 224) were recruited in Manaus/Amazonas State (130 blood donors from the Hematology and Hemotherapy Foundation from Amazonas/HEMOAM; 60 subjects from outpatient clinic) and in Eirunepe city (n = 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 41 publications
(41 reference statements)
9
50
0
5
Order By: Relevance
“…Recent evaluations of HDV prevalence are consistent with high endemicity, with HDV seropositivity rates ranging from 8,5% of HBsAg-positive asymptomatic blood donors to 65% in HBsAg-positive hospital outpatients (120). High HDV prevalence rates are also reported in the Amazonian areas of Venezuela and Colombia, where the infection is, as in Brazil, caused by HDV-3 and associated with fulminant hepatitis outbreaks (121).…”
Section: The Case Of Low Endemicity Regionsmentioning
confidence: 85%
“…Recent evaluations of HDV prevalence are consistent with high endemicity, with HDV seropositivity rates ranging from 8,5% of HBsAg-positive asymptomatic blood donors to 65% in HBsAg-positive hospital outpatients (120). High HDV prevalence rates are also reported in the Amazonian areas of Venezuela and Colombia, where the infection is, as in Brazil, caused by HDV-3 and associated with fulminant hepatitis outbreaks (121).…”
Section: The Case Of Low Endemicity Regionsmentioning
confidence: 85%
“…Genotype C HBV was associated with more adverse outcomes than genotype B in chronic HDV infection. In a study from Amazon region, only HDV-3 and HBV genotype A, D and F were identified [98,99]. A recent study compared the infectivity of HBV genotypes in HDV coinfection.…”
Section: Discussionmentioning
confidence: 97%
“…6,14 The incidence of HBV is increasing dramatically in northern and central Europe because of infected individuals emigrating from endemic regions as well as increased rate of IV drug abuse. 15 Co-infection with HDV is common in Africa and Middle east however in USA coinfection with HDV is restricted to individuals with IV drug abuse or others at high risk.…”
Section: Discussionmentioning
confidence: 99%